2017
DOI: 10.1097/scs.0000000000003394
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Skin Defects on the Mid and Lower Face Using Expanded Flap in the Neck

Abstract: The application of expanded flaps in the neck is proved to be an effective way of repairing facial defects on the mid and lower face. The technique is remarkably reliable in resurfacing the peripheral facial esthetic units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, the use of a flap has also been associated with some complications such as necrosis, infection, and hematoma. Hu et al ( 9 ) suggested that the necrosis of the expanded flap was related to its length-to-width ratio and the presence or absence of well-known arteries. Moreover, Chen and colleagues ( 10 ) argued that changing the blood flow of the expanded flap could prevent the necrosis of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of a flap has also been associated with some complications such as necrosis, infection, and hematoma. Hu et al ( 9 ) suggested that the necrosis of the expanded flap was related to its length-to-width ratio and the presence or absence of well-known arteries. Moreover, Chen and colleagues ( 10 ) argued that changing the blood flow of the expanded flap could prevent the necrosis of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…The nasal area is anatomically complex, for its comprehensive reconstruction an integral understanding is necessary, this being a three-dimensional structure with its bone and cartilaginous support, a mucous lining and a skin covering, and according to the condition of these structures it is the surgical and reconstructive challenge to face. The general principles of reconstruction are also applicable to the nasal area as long as we understand and respect the nasal units and subunits [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Many methods, such as full-thickness skin grafting, local or free flap, and expanded flap, have been used to reface the defect of lower part of the face and neck. [1][2][3] The cervical area is considered as the best donor site for the face reconstruction. But with scar contracture or tumor invasion, cervical area might be compromised and no longer available.…”
mentioning
confidence: 99%
“…Patients’ appearance and function can be severely undermined due to these injuries or lesions. Many methods, such as full-thickness skin grafting, local or free flap, and expanded flap, have been used to reface the defect of lower part of the face and neck 1–3 . The cervical area is considered as the best donor site for the face reconstruction.…”
mentioning
confidence: 99%